Applications of deterministic and stochastic rock physics modelling to anisotropic velocity model building. (7th January 2013) - Bachrach, Ran; Osypov, Konstantin; Nichols, Dave; Yang, Yi; Liu, Yangjun; Woodward, Marta
ABSTRACT Modern anisotropic depth imaging requires transverse isotropy velocity models. Because the surface seismic experiment alone cannot uniquely determine all transverse isotropy parameters, additional information is required. Traditional methods that use checkshots can only constrain anisotropy locally near the well and thus model building requires 3D extrapolation of well data. We propose to use rock physics. Rock physics compaction modelling of shales and sandy shales can be used to constrain and predict anisotropic parameters of sediments whose depositional environment is governed by compaction. In this study, we present several applications of rock physics modelling to anisotropic velocity model building. We show how both deterministic and stochastic rock physics modelling can be used for initial anisotropic velocity model building and as a constraint for anisotropic parameter estimation. In all cases, all predicted anisotropy models are physical and realizable in terms of effective medium theory and do not violate elasticity theory.